TINGKAT KEPUASAN MAHASISWA DALAM MENGGUNAKAN MEDIA SOSIAL SNAPCHAT DI PEKANBARU - Anggi Pradita; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The development of the internet relatively faster than the other medias. internet is used as communication media through facilities inside. Social media currently took attention from society especially scholarship student. Social media has been considered could be a container for creations, ideas, responses, even opinions. some of those as facebook, path, instagram, twitter and etc. But the most popular social media are used by student nowadays is snapchat. Snapchat is an application thats suppose to share messages with photos and videos in an unique way. To used phenomenal social media snapchat, student use snpachat to express themselves everyday. Because of that for study the level of student satisfaction in using social media snapchat. This study is using Uses and Gratification theory, this theory declare that audiences are using media actively. the purpose of this study is to determine the value of level of student satisfaction in using social media snapchat in Pekanbaru.The type of this study is descritive quantitative research, the technique of collecting data in this study is using questionnaire. Samples of this study as much as 166 respondents that founded by using unknown population formula with 99% accuracy level. The samples taken by accidental sampling method. To find out how much the gratification level, this study used ‘uses and gratification’ model. To Proccessing the questionnaire datas, were performed by using Statistictal Product and Service Solution (SPSS) Windows program v.20.By looking at the ratio of gratification motive scores obtained with the needs of users by using social media snapchat, the result mean value calculation GS (3,137) is smaller than the value of GO (3,189). Which means there is a discrepancy gratification because of the needs earned more than the desired needs. The result showed that the gratification level of using social media snapchat by students in pekanbaru is indicated at high category with 3,163 calculation value, data processing is seen by four indicators, namely information, personal identity, social interaction, and entertainment. therefore, it means social media snapchat can satisfy the users.Keyword: Snapchat, Social Media